Is Distance Education Fun? The Implications of Undergraduates' Epistemological Beliefs for Improving Their Engagement and Satisfaction with Online Learning - Kieron Sheehy; Abigail Mclanachan; Ale Okada; Mimi Tatlow-Golden; Stephen Harrison (Athens Institute for Education and Research, 2023)
The epistemological beliefs of students are an important area for higher education research. This paper firstly reports on a research review concerning the impact of epistemological beliefs on academic outcomes. This review indicates that students' epistemological beliefs are an influence on their engagement with learning and academic success, and that educators should consider them in developing learning experiences. This issue became particularly pertinent in the context of a global pandemic that necessitated an international trend in moving to online distance education, where student disengagement is more likely to occur. However, research into distance education students' epistemological beliefs emerged as an under-researched field. Consequently, an empirical questionnaire study was conducted with data collected from 550 distance education students. A principal component analysis indicated that particular epistemological beliefs were significantly associated with students' enjoyment of studying online. Their beliefs regarding the role of fun in online learning materials and activities are discussed, and the usefulness of considering fun and epistemological beliefs as factors within distance learning in higher education is highlighted.